2005
DOI: 10.1128/jvi.79.11.6732-6740.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of the E1 E4 Protein in the Differentiation-Dependent Life Cycle of Human Papillomavirus Type 31

Abstract: The most highly expressed protein in the productive life cycle of human papillomaviruses (HPVs) is E1 ∧ E4, but its function is not well understood. To investigate the role of E1 ∧ E4, we undertook a genetic analysis in the context of the complete HPV type 31 (HPV31) genome. A mutant HPV31 genome (E4M9) was constructed that contained a stop codon in the E4 open reading frame at amino acid 9 and was silent in the overlapping E2 coding sequence. Wild-type and mutant genomes were transfected into normal human for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 51 publications
2
91
2
3
Order By: Relevance
“…As a result, the virus copy number amplifies from 50-200 copies to several thousands of copies per cell. 63 This replication strategy adopted by HPV reduces expression of proteins in undifferentiated cells and only intensifies the expression of their proteins, particularly those that comprise the viral capsid; in the more differentiated cells, the replication strategy functions as an escape mechanism of the immune response.…”
Section: Differentiation-dependent Phasementioning
confidence: 99%
“…As a result, the virus copy number amplifies from 50-200 copies to several thousands of copies per cell. 63 This replication strategy adopted by HPV reduces expression of proteins in undifferentiated cells and only intensifies the expression of their proteins, particularly those that comprise the viral capsid; in the more differentiated cells, the replication strategy functions as an escape mechanism of the immune response.…”
Section: Differentiation-dependent Phasementioning
confidence: 99%
“…The E4 protein sequesters the CDK1/Cyc B1 complex (CDK, Cyclin dependent kinase and Cyc, Cyclin) onto the cytokeratin network, preventing their nuclear accumulation and therefore inducing inhibition of the G2/M transition of the cell cycle (Davy et al, 2002;Nakahara et al, 2002) and allowing viral and genomic DNA replication. The HPV16 E4 coding region possesses a splicing enhancer element required for the early viral mRNA splicing (Rush et al, 2005), especially for the expression of late viral transcripts of E1^E2, E1, E4 and E5, thus regulating the viral DNA amplification (Wilson et al, 2005).…”
mentioning
confidence: 99%
“…It has been observed that the viral integration occurs mainly between E1-E2 ORFs, event that produces the loss of E2 and E4 genes expression. Thus, the loss of E2 and E4 genes generates a down-replication of the viral genome, G2 arrest, and E6 and E7 over-expression (Jeon & Lambert, 1995;Wilson et al, 2005). Thus, the integration of the HPV DNA in the host genome represents an important event in cervical carcinogenesis (Pett & Coleman, 2007), as this may cause cellular immortalization (Band et al, 1990;Jeon & Lambert, 1995;Münger et al, 1992;zur Hausen, 2000), reduction of cellular differentiation, cellular dysplasia and TNF-α non-responder cells (TNF, Tumor Necrosis Factor) (Syrjänen & Syrjänen, 1999;zur Hausen, 2000).…”
mentioning
confidence: 99%
“…It is expressed as an E1^E4 fusion protein from spliced transcripts formed between the N terminus of the E1 open reading frame and almost the complete open reading frame of E4 (21). The precise function of E4 has not been defined, but loss of expression of the full-length E1^E4 polypeptide has a severe adverse effect on viral genome amplification of HPV type 16 (HPV16), HPV18, and HPV31 following introduction of mutant genomes unable to support E1^E4 expression into keratinocytes and subsequent induction of cellular differentiation (20,38,39). Failure to complete the vegetative stage of the virus life cycle is also the outcome of loss of E1^E4 expression in rabbit papillomas induced by a mutant cottontail rabbit papillomavirus genome (22).…”
mentioning
confidence: 99%